Entertainment in Russian Regions: Structure, Factors and Preferences - Inna B. Nazarova (Регионология, 2025)
Introduction. Entertainment plays a key role in modern lifestyles, acting as an important component of leisure and well-being. Despite their importance, comprehensive research on entertainment consumption in Russia remains limited. This paper aims to fill this gap. We analyze the structure of entertainment preferences among the country’s residents with a focus on socio-demographic and regional differences.